Collagen – a newly discovered major player in protein corona formation on nanoparticles. Issue 9 (17th February 2022) - Upreti, Tushar; Wolfe, Kathryn M.; Van Bavel, Nicolas; Anikovskiy, Max; Labouta, Hagar I.
Abstract : Spectroscopic investigation of protein corona on gold nanoparticles reveals largely different affinities of the plasma protein albumin and the extravascular protein collagen resulting in dynamic exchange of the proteins upon sequential exposure. Abstract : Tracking protein corona (PC) formation on the surface of nanoparticles (NPs) is a prerequisite for successful design of next generation nanocarriers with predictable fate and behavior. However, PC formation has mostly been investigated for plasma proteins without considering potential competition with the extravascular proteins either when the NPs exit the blood circulation or when they are injected extravascularly. This study investigates the deposition of collagen, an extravascular protein that is the most abundant in the body, and albumin, the most abundant vascular protein, on the surface of gold (Au) NPs using UV-Vis and fluorescence spectroscopy with the support of mathematical modeling. Moreover, a novel spectroscopic approach to determining the protein–NP binding constants and surface occupancy is presented. We show that albumin and collagen have drastically different affinities for Au NPs. Our data demonstrates that the surface bound albumin can be exchanged with collagen confirming the dynamic nature of PC in the extravascular milieu. We propose that future PC investigations in the framework of drug delivery should rely on understanding of the NP transit in the body, and include competition experiments with relevant vascular and extravascular proteins. Furthermore, our results that reveal very strong binding of collagen to AuNPs may lay the foundation for designing long circulating collagen-coated NPs with minimal surface adsorption of plasma proteins and, thus, reduced immune recognition.